AN STUDY OF INTERPRETING BETWEEN INDONESIA-ENGLISH AND ENGLISH-INDONESIA AT STUDENT OF MAN 1 MAKASSAR - Umi Rosidah; Kamsinah , (ETERNAL (English, Teaching, Learning and Research Journal), 2017)
The objective of this research was to find out the students’ competence in interpreting Indonesia into English and English into Indonesia. This research was conducted to the first year students of MAN 1 Makassar, academic year 2015/2016. This research employed descriptive method. The population is all of students at the first year of Man 1 Makassar where the class X consist 154 students which divided in 6 classes. So the sample is taken by simple random sampling. The researcher took 31 students as sample. The instruments of this research were an essay test and questionnaire. The result of the data indicated that used comparative mean, mean 1 and mean 2 which researcher was found the result of data analysis is the overall result of Interpreting Indonesia-English test is 176.2 or mean is 5.68 and the overall result of Interpreting English to Indonesia test is 185.6 or mean is 5.98. Based on the finding and discussion of the research, the researcher concluded that the first students of MAN 1 Makassar need more time, and focus more on grammar in interpreting Indonesia into English. Therefore, the researcher suggested to the teacher gave more exercises, guidance and motivation in translation teaching.